PENGARUH TERAPI KOMBINASI INHALASI AROMATERAPI LAVENDER DAN MUSIK TERHADAP KECEMASAN PASIEN HEMODIALISA - Arly, Vivian Meika; Pemila, Uke; Antoro, Budi (Universitas Aufa Royhan, 2024)
Chronic Renal Failure is a state of progressive reduction in kidney function which is signalled by a decrease in Glomerular Filtration Rate (GFR) <60 mL/min/1.73 m2 for ≥ 3 months. Haemodialysis aims to remove metabolic waste carried out for 3-5 hours with a frequency of 2-4 times a week which is lifelong, this causes anxiety. This study aims to see the effect of combined music inhalation therapy and lavender aromatherapy on the anxiety of chronic renal failure patients who do haemodialysis. This type of research is quantitative research using the Quasi experimental non-equivalent control design method. The population of this study were chronic renal failure patients who performed haemodialysis at the Hemodialysis Unit of Dr. H. Abdul Moeloek Hospital. The sample of 86 respondents was divided into 43 respondents of the intervention group and 43 respondents of the control group with non-probability purposive sampling technique based on inclusion and exclusion criteria. The research instrument used was the Hamilton Anxiety Rating Scale (HARS). The results of the study obtained a p-value of 0.000 (p-value <0.05) using the Mann Whitney U Test which shows that there is a Significant Effect of Lavender Aromatherapy and Music Inhalation Combination Therapy on Anxiety of Chronic Kidney Failure Patients Carrying out Hemodialysis at Dr. H. Abdul Moeloek Lampung Hospital in 2024. It is hoped that this therapy can be applied independently either in the haemodialysis unit or at home to reduce anxiety.